Efecto del poliacrilato de potasio con distintos intervalos de riego por goteo sobre la producción de pepino en Machala. - Honores Ochoa, Jimmy Andres; Roblez Vaca, Jonathan Cristian (Machala : Universidad Técnica de Machala, 2023)
The present research was conducted at the Technical University of Machala in the Faculty of Agricultural Sciences with the objective of evaluating the impact of potassium polyacrylate applied with different drip irrigation intervals on cucumber crop production. A completely randomized block factorial experimental design with two factors was employed: the application of hydrogel (with and without) and four irrigation intervals (every 4, 5, 6, and 7 days). This design resulted in a total of 24 experimental units. The analysis of variance (ANOVA) revealed that, although the overall model was significant, the individual factors and their interaction did not show statistically significant effects on the variables of fruit weight, length, and diameter. However, there was a trend indicating that the use of hydrogel improved the weight and length of the fruits, especially under less frequent irrigation conditions. This suggests that hydrogel may offer particular benefits in situations of water stress. In terms of Brix degrees, which measure the concentration of sugars in the fruit, significant differences were found based on the use of hydrogel and irrigation frequency. Brix degrees were higher in treatments that included hydrogel and in those with irrigation frequencies of every 4 and 6 days. This finding indicates greater efficiency of hydrogel treatment in improving the sweetness and ripeness of the fruit. Additionally, the quality of production showed significant variations. First-grade fruits were more abundant with an irrigation frequency of every 5 days. On the other hand, the use of hydrogel improved the proportion of second-grade fruits and reduced the number of rejected fruits due to defects. These results are consistent with previous studies that have demonstrated the hydrogel's ability to improve water retention and favor crop growth under water stress conditions. Implementing hydrogel in combination with adequate irrigation intervals can significantly improve the production and quality of cucumbers under water stress conditions. This suggests its potential as an effective tool to mitigate the effects of water stress in horticultural crops. Given the evidence of the benefits of hydrogel in water retention and crop yield improvement, it is recommended to continue with additional research exploring different doses of hydrogel and its application to other crops. These studies will help validate the obtained results and optimize agricultural practices in the Machala region and in areas with similar conditions. The extension of these studies could provide a solid basis for recommending the use of hydrogel as a standard practice to improve the sustainability and efficiency of agriculture in regions prone to water stress.
La presente investigación se llevó a cabo en la Universidad Técnica de Machala en la facultad de ciencias agropecuarias teniendo como objetivo evaluar el impacto del poliacrilato de potasio aplicado con diferentes intervalos de riego por goteo sobre la producción del cultivo de pepino empleando un diseño experimental factorial en bloques completamente al azar con dos factores: la aplicación de hidrogel (con y sin) y cuatro intervalos de riego (cada 4, 5, 6 y 7 días). Este diseño resultó en un total de 24 unidades experimentales. El análisis de varianza (ANOVA) realizado reveló que, aunque el modelo general fue significativo, los factores individuales y su interacción no mostraron efectos estadísticamente significativos en las variables de peso, longitud y diámetro del fruto. Sin embargo, se observó una tendencia en la que el uso del hidrogel mejora el peso y la longitud de los frutos, especialmente en condiciones de riego menos frecuente. Esto sugiere que el hidrogel puede ofrecer beneficios particulares en situaciones de estrés hídrico. En términos de grados Brix, que miden la concentración de azúcares en el fruto, se encontraron diferencias significativas en función del uso de hidrogel y la frecuencia de riego. Los grados Brix fueron más altos en los tratamientos que incluían hidrogel y en aquellos con frecuencias de riego de cada 4 y 6 días. Este hallazgo indica una mayor eficiencia del tratamiento con hidrogel para mejorar la dulzura y madurez del fruto. Además, la calidad de la producción mostró variaciones significativas. Los frutos de primera calidad fueron más abundantes con una frecuencia de riego de cada 5 días. Por otro lado, el uso de hidrogel mejoró la proporción de frutos de segunda calidad y redujo el número de frutos rechazados debido a defectos. Estos resultados son consistentes con estudios previos que han demostrado la capacidad del hidrogel para mejorar la retención de agua y favorecer el crecimiento de cultivos en condiciones de estrés hídrico. La implementación de hidrogel en combinación con intervalos de riego adecuados puede mejorar significativamente la producción y calidad del pepino bajo condiciones de estrés hídrico. Esto sugiere su potencial como una herramienta eficaz para mitigar los efectos del estrés hídrico en cultivos hortícolas. Dada la evidencia de los beneficios del hidrogel en la retención de agua y la mejora del rendimiento de los cultivos, se recomienda continuar con investigaciones adicionales que exploren diferentes dosis de hidrogel y su aplicación en otros cultivos. Estas investigaciones ayudarán a validar los resultados obtenidos y a optimizar las prácticas agrícolas en la región de Machala y en áreas con condiciones similares. La extensión de estos estudios podría proporcionar una base sólida para recomendar el uso de hidrogel como una práctica estándar para mejorar la sostenibilidad y eficiencia de la agricultura en regiones propensas al estrés hídrico.
Keywords: HIDROGEL; INTERVALO; CALIDAD; HIDRICO